Decreased vigorous physical activity in school-aged children with HIV in Johannesburg, South Africa - Wong, Marcia (J Pediatr, 2016)
OBJECTIVE: To describe physical activity in South African children with and without HIV. STUDY DESIGN: Study measurements were obtained in 218 children with perinatal HIV and 180 children without HIV aged 5–10 years in a study conducted in Johannesburg, South Africa. Weight-for-age (WAZ) and height-for-age (HAZ) Z-scores, and frequency and duration of moderate and vigorous physical activity, and sedentary behavior, were obtained. Measures were compared between children with and without HIV. RESULTS: WAZ and HAZ were significantly lower for children with HIV compared with those without HIV. Among children who attended school, less children with HIV participated in physical education (41 vs. 64%, p=0.0003) and organized after-school sports (38 vs. 64%, p<0.001) than children without HIV. The proportion of children in both groups meeting World Health Organization recommendations for physical activity was similar (84% overall). However, girls with HIV spent less time in vigorous physical activity than girls without HIV (420 vs. 780 minutes/week, p=0.001). This difference remained significant even when girls with medical conditions with potential to limit physical activity were excluded, and after adjusting for age. Time spent in sedentary behaviors did not differ significantly between the groups. CONCLUSION: Although children with HIV with well-controlled disease after initiating antiretroviral therapy early in life achieve high levels of physical activity, vigorous physical activity is lower in girls with HIV than in healthy controls. This may reflect lower participation in school-based physical education and organized after-school physical activity.